EL CHILAMATAL: HISTORY OF SOCIAL MOBILIZATIONS FOR LAND RESOURCE IN THE VALLEY OF ZAPOTITÁN 1913-1936 - Sevillano Payes, Denis (2023)
This article explains how communities distant from coffee areas in the contexts of implementation of the agro-export State, crisis and agrarian reform, mobilized for the land resource in El Salvador. To answer this question, they are presented from the local perspective, the impact of the use of the land resource on the peasant mobilizations that took place in Chilamatal-Ciudad Arce between 1913-1936, a town located in the Zapotitán Valley, which at the time in question was made up of the latifundium as the predominant unit. of land tenure.